The Importance of Information in Shaping Sustainable Human Behaviour - Macijauskaitė–Daunaravičienė, Ugnė; Mikalauskienė, Asta (Vilnius University Proceedings, 2023)
As the climate crisis has become a growing issue in recent decades, sustainable development has become a focus of attention for the international community. In 2015, the United Nations launched the Sustainable Development Goals (SDGs), which call on countries to grow their economies and meet their social needs with the least possible damage to the environment. The aim is to preserve natural resources for future generations. As a result, various policies have been introduced and integrated in different countries to address the problematic aspects of sustainable development. One of the most important catalysts for sustainable development is the promotion of sustainable consumer behaviour. Sustainability requires a fundamental change in individual behaviour. Achieving Sustainable Development Goals will help ensure that future generations can meet their needs. Research to date shows that individuals still do not behave sustainably. Understanding what factors influence sustainable individual behaviour and how to persuade people to behave sustainably is therefore of growing scientific interest. The external and internal factors influencing an individual’s behaviour are based on information sources. The aim is to explain how, in what way, and at what level, initial information data is perceived and used by the individual. As a result, a study was carried out to investigate the impact of information in shaping sustainable individual behaviour in Lithuania